2023
DOI: 10.1097/rlu.0000000000004628
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT Imaging of Severe Polymyalgia Rheumatica

Abstract: A 68-year-old woman was referred for an 18 F-FDG PET/CT for evaluation of arthralgia and raised inflammatory markers, which demonstrated intense FDG activity (SUV max , 25.5) at numerous periarticular and extra-articular sites including the cervical and lumbar interspinous bursae, lumbar facet joints, bilateral ischial tuberosities, and greater trochanters and the aorta consistent with active polymyalgia rheumatica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…2 Studies have shown that the schwannomas had a wide variation in SUV max ranging from 1.5 to 17.3, which may be related to different degrees of cellularity, microvascular density, vascular permeability, or presence of peritumoral lymphoid cuffs. [3][4][5][6][7][8] The low metabolic manifestations of current case in PET findings are difficult to distinguish from some benign tracheal tumors and low-grade malignant tumors, such as papilloma, leiomyoma, hamartoma, adenoid cystic carcinoma, low-grade mucoepidermoid carcinoma, carcinoid, mucosa-associated lymphoid tumor. 9,10 Nuclear medicine physicians should be familiar with the PET/CT imaging findings of schwannoma.…”
Section: Figurementioning
confidence: 80%
“…2 Studies have shown that the schwannomas had a wide variation in SUV max ranging from 1.5 to 17.3, which may be related to different degrees of cellularity, microvascular density, vascular permeability, or presence of peritumoral lymphoid cuffs. [3][4][5][6][7][8] The low metabolic manifestations of current case in PET findings are difficult to distinguish from some benign tracheal tumors and low-grade malignant tumors, such as papilloma, leiomyoma, hamartoma, adenoid cystic carcinoma, low-grade mucoepidermoid carcinoma, carcinoid, mucosa-associated lymphoid tumor. 9,10 Nuclear medicine physicians should be familiar with the PET/CT imaging findings of schwannoma.…”
Section: Figurementioning
confidence: 80%